2018
DOI: 10.1016/j.rmed.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

High risk of subclinical atherosclerosis in COPD exacerbator phenotype

Abstract: It is not known whether COPD exacerbations contribute to an increased vascular risk already associated with the disease. For this reason, we prospectively evaluated 127 patients referred for a monographic COPD consultation. We classify as exacerbators those who had experienced two or more moderate exacerbations in the previous year, or who had had a hospital admission. All underwent a blood analysis, respiratory function tests, global cardiovascular and coronary risk estimates (with four of the most frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In patients with COPD, asymptomatic CVD progression significantly heightens the risk of comorbid CVD-associated mortality, and this is largely due to these patients being at heightened risk of atherosclerosis, due to the persistent systemic inflammation associated with this disease. Atherosclerosis is defined as a condition that causes the innermost layer of a blood vessel (endothelial layer), to become narrowed and hardened due to a build-up of fatty tissue and subsequent plaque formation, possibly leading to cardiovascular complications such as vascular occlusions and ischaemic stroke [85]. Key risk factors of atherosclerosis include cigarette smoking, elevated BP and high cholesterol associated with poor lifestyle (e.g.…”
Section: Atherosclerosis and Impaired Blood Vessel Function In Copdmentioning
confidence: 99%
“…In patients with COPD, asymptomatic CVD progression significantly heightens the risk of comorbid CVD-associated mortality, and this is largely due to these patients being at heightened risk of atherosclerosis, due to the persistent systemic inflammation associated with this disease. Atherosclerosis is defined as a condition that causes the innermost layer of a blood vessel (endothelial layer), to become narrowed and hardened due to a build-up of fatty tissue and subsequent plaque formation, possibly leading to cardiovascular complications such as vascular occlusions and ischaemic stroke [85]. Key risk factors of atherosclerosis include cigarette smoking, elevated BP and high cholesterol associated with poor lifestyle (e.g.…”
Section: Atherosclerosis and Impaired Blood Vessel Function In Copdmentioning
confidence: 99%
“…The prevalence of CVD was significantly higher in participants with PRISm results and GOLD stage II COPD, leading them to conclude that people with poor spirometry, especially those with moderate COPD and patients with PRISm, have a higher incidence of CVD compared to those with normal spirometry, such that having COPD increases the risk of developing CVD 42 . A previous study by our group analysed CVR in the total sample of COPD patients and found elevated values in all the scales used, both in exacerbator and non-exacerbator patients, but there were no significant differences according to clinical phenotypes 43 .…”
Section: Discussionmentioning
confidence: 78%
“…Subclinical atherosclerosis of the carotid arteries is more pronounced in patients with COPD exacerbation. Patients with COPD exacerbations have a higher risk of vascular ischemic events [45]. A large study conducted in the United States found that COPD exacerbations were associated with an increased incidence of acute cardiovascular events within 30 days and one year [46].…”
Section: Discussionmentioning
confidence: 99%